Alternative Assessment (Assessing Students by Using Observation Project) - Fifi Nur Ulwiyah; Mimi Jamilah (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2024)
In language acquisition, instruction and evaluation are two significant components within the educational domain. Numerous educators have conducted assessments of English in classroom instruction. Various forms of assessment exist in the teaching and learning process of English. Employing observation-project presentation evaluation proves to be highly beneficial for both educators and learners within the framework of English instruction. By undertaking their own project tasks, students can articulate and elucidate their work proficiently, as they are afforded time to prepare their presentations. Composing their thoughts before to the presentation is the most effective method for students to enhance their English proficiency.